A Review of the GSTM1 Null Genotype Modifies the Association between Air Pollutant Exposure and Health Problems - Dwi Aris Agung Nugrahaningsih; Hevi Wihadmadyatami; Sitarina Widyarini; Rahmi Ayu Wijayaningsih (International Journal of Genomics)
Air pollution is one of the significant environmental risks known as the cause of premature deaths. It has deleterious effects on human health, including deteriorating respiratory, cardiovascular, nervous, and endocrine functions. Exposure to air pollution stimulates reactive oxygen species (ROS) production in the body, which can further cause oxidative stress. Antioxidant enzymes, such as glutathione S-transferase mu 1 (GSTM1), are essential to prevent oxidative stress development by neutralizing excess oxidants. When the antioxidant enzyme function is lacking, ROS can accumulate and, thus, cause oxidative stress. Genetic variation studies from different countries show that GSTM1 null genotype dominates the GSTM1 genotype in the population. However, the impact of the GSTM1 null genotype in modifying the association between air pollution and health problem is not yet clear. This study will elaborate on GSTM1’s null genotype role in modifying the relationship between air pollution and health problems.